Extreme long‐term voice outcomes after concurrent chemoradiotherapy for advanced non‐laryngeal head and neck cancer: Eight‐year post‐treatment analysis. (6th September 2018) - Davies‐Husband, Cameron; Murphy, Jennifer; Kelly, Charles; Drinnan, Michael; Paleri, Vinidh
Abstract : Background: The long‐term effect of concurrent chemoradiation on voice outcomes in the context of non‐laryngeal head and neck cancer is not established. Methods: A prospective, observational study to evaluate the voice quality in disease‐free patients receiving concurrent chemoradiation for advanced non‐laryngeal squamous cell carcinoma of the upper aerodigestive tract. Voice assessment occurred at four distinct time‐points: pretreatment, 3, 12 and 92.6 months (mean) post‐treatment in 34, 21 and nine patients, respectively. The authors used a combination of subjective (VoiSS questionnaire), expert rater‐assessed (GRBAS scale) and acoustic analysis of the fundamental frequency to assess voice outcomes. Ethical approval was obtained from the United Kingdom National Research Ethics Service. Results: Both the VoiSS impairment and GRBAS domains continued to deteriorate over time from pre‐treatment to 92.6 months post‐treatment ( P  = 0.03). There was a strong correlation between increase in total VoiSS and GRBAS scores ( r  = 0.93). Acoustic analysis demonstrated no statistically significant variation in fundamental frequency. Conclusion: Radiation therapy for advanced non‐laryngeal head and neck has a significant, deleterious effect on voice, which is apparent up to eight years post‐treatment.